Love Curriculum in Islamic education: Fostering Tolerance and Religious Moderation - Ahmad Hanif Fahruddin; Afandi Afandi; Mufiqur Rahman; Masrufah Masrufah; Mo’tasim Mo’tasim; Indhra Musthofa (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study explores the implementation of the Love Curriculum, with a particular focus on its integration at Pesantren Al-Amien Prenduan. Using a qualitative approach with document analysis, field observations, and semi-structured interviews with teachers and students, the study investigates how the Love Curriculum’s nine core values empathy, compassion, tolerance, justice, respect, humanity, cooperation, responsibility, and creativity are practiced within pesantren education. The findings reveal that Al-Amien embeds these values not only in formal classroom learning but also in dormitory life, communal worship, and student organizations, creating an environment that nurtures students’ intellectual, moral, and spiritual growth. The novelty of this study lies in its examination of how pesantren education, traditionally rooted in Islamic values, adapts and operationalizes a state-issued curriculum to promote religious moderation, multiculturalism, and the Profil Pelajar Pancasila. Unlike previous studies that analyze tolerance education primarily in public schools, this research demonstrates that pesantrens can serve as unique models for integrating love-based pedagogy with religious and national identity. The study concludes that the Love Curriculum at Al-Amien contributes to countering intolerance, strengthening national commitment, and cultivating inclusive, socially responsible graduates thereby offering a replicable model for Indonesian and global Islamic education in the era of rapid social change.